Pneumomediastinum After COVID-19 - Kasey B. Johnson BS; Vanessa G. Carroll MD; Hinah G. Parker MD (SAGE Publishing, 2022)
A preadolescent female presented to the emergency department with an acute asthma exacerbation. Chest radiograph and computed tomography scan showed extensive pneumomediastinum with a small pneumopericardium without a distinct source for this air leak. The patient was admitted for noninvasive monitoring, analgesia, and high concentration oxygen. Serial chest radiographs showed marked improvement following high concentration oxygen, and she was discharged on hospital day 3. Spontaneous pneumomediastinum and pneumopericardium are rare complications of asthma that can often be managed conservatively but should be considered on the differential for this patient population, and may be a complication of COVID-19.